Local predation pressure predicts the strength of mobbing responses in tropical birds - Luis SANDOVAL, David R. WILSON (Current Zoology, 2012)
Many birds join cooperative mobbing aggregations and collectively harass predators. Individuals participating in these ephemeral associations benefit by deterring the predator, but also incur energetic costs and increased risk of predation. Explaining the evolution of mobbing is challenging because individuals could prevail by selfishly seeking safety while allowing others to mob. An important step in understanding the evolution of mobbing is to identify factors affecting its expression. The ecological constraints model suggests that animals are more likely to cooperate under adverse environmental conditions, such as when local predation pressure is high. We tested this prediction by comparing the mobbing responses of several species of birds to the local abundance of their primary predator, the ferruginous pygmy-owl Glaucidium brasilianum. We used acoustic playback to elicit mobbing responses in environments where owls were common, uncommon, or rare. Stimuli were either the song of a ferruginous pygmy-owl or the mobbing calls of three of the owl’s common prey species. During each playback, we characterized mobbing responses by noting the number of species and individuals that approached the loudspeaker, as well as the closest approach by any bird. Mobbing responses to both stimuli were strong in locations where Ferruginous Pygmy-owls were common, intermediate where owls were uncommon, and weak where they were rare. This pattern persisted even after controlling for differences in species richness and composition among the three environments. Results support the ecological constraints model and provide strong evidence that intense predation pressure increases the expression of cooperative mobbing in tropical birds [Current Zoology 58 (5): 781-790, 2012].